PRKCD/PKCδ contributes to nephrotoxicity during cisplatin chemotherapy by suppressing autophagy - Zhang, Dongshan (Autophagy, 2017)
Nephrotoxicity is a major side effect during chemotherapy with cisplatin and related platinum compounds. Previous work unveiled a role of PRKCD/PKCδ (protein kinase C delta) in cisplatin-induced nephrotoxicity; however, the underlying mechanism was largely unknown. Our recent work showed that PRKCD may suppress macroautophagy/autophagy, a cytoprotective mechanism, to promote kidney tubule cell death during cisplatin treatment. Interestingly, PRKCD may do so by phosphorylating AKT, which further phosphorylates MTOR to repress ULK1.